ANALISIS TINGKAT PENERAPAN TEHKNOLOGI BUDIDAYA LEBAH MADU ALUMNI PETALIH “UD. AMANAH” DIDUSUN JAYAN DESA BOROBUDUR KECAMATAN BOROBUDUR KABUPATEN MAGELANG - Siti Hamidah; Vini Arumsari; Momod Nugroho (Jurnal Dinamika Sosial Ekonomi, 2010)
Technology Application level analysis of Honey Bee Farming liaising Alumni "UD. Amanah” in village Distict Jayan Borubudur Magelang District. This study to (1 )Analyzing the Application of honey bee cultivation technology training alumni "UD.Amanah” (2) Analyzing the influence of age, education level, exprience, training intensity and the number of levels implementation honey bee cultivation technology training alumni "UD.Amanah” (3) Analyzing the honeybee cultivation undertaken by graduate training “UD.Amanah”. The study was carried out by using Case study method. Kind of data is primary data and secondary data. Analyzing level for the application of honeybee cultivation technology using a likert scale score, to analize Influence of age, education level, exprience, training intensity and the number of levels step using multiple liner regression equation, to analize honeybee cultivated using break even point analysis. The results showed that the level of the application of honeybee cultivation technology training alumni “UD.Amanah” in the high category, indicated by an average score of 61.57 (93.29%). Factors age, education level, exprience, training intensity and the number of levels step together against the application of honeybee ccultivation technology for 87,4%, intensity training is the most influential variabel of the 5 other variables. Honeybee busies be at profit area with the average honey product at first period1,1 kg/stup and number of stup 23 stop with profit Rp 738. 700/ period and second period 1,2 and number of stup 30 stup with profit Rp 823.800/ period.Keyword : Level of implementation